LEGAL PROSPECTS FOR THE DEVELOPMENT OF FOOD SECURITY IN THE ARCTIC ZONE OF THE RUSSIAN FEDERATION - Galina V. Goncharuk (Russian Studies in Law and Politics, 2023)
The relevance of the issue studied in the article lies in the fact that the achievement of food security in the territories of the Arctic zone of the Russian Federation (hereinafter also AZRF), to which there is no year-round access by land transport, is a challenge for the state in matters of ensuring national security. One of the ways to achieve food security in the Russian Arctic is the northern delivery. The purpose of the study is to propose a number of directions for the development of Russian Arctic legislation based on the analysis of the legal documents of the Russian Federation, international legal documents, as well as the positive experience of Canada in the field of food security regulation. The article considers the positive experience of Canada in regulating public relations in the field of pursuing a centralized food security policy, as well as in organizing public greenhouses and gardens, and analyzes the possibility of applying these foreign development directions in the legislation of the Russian Federation. In the final part of the article, the author comes to the conclusion that it is necessary to apply a more systematic approach in the field of food security, linking legal documents adopted in various areas of public relations (health, social sphere, science and innovation in agriculture, development of transport infrastructure and rural settlements), into a single concept, a common action plan to achieve the global goal - food security. A separate place in this concept should be occupied by the processes of organizing the northern delivery and measures to develop their own agricultural production of vegetables and fruits in the territory of the Russian Arctic, according to the experience of Canada.